Hubungan Antara Self Esteem dengan Optimisme Masa Depan Pada Siswa Santri Program Tahfidz di Pondok Pesantren Al Muayyad Surakarta dan Ibnu Abbas Klaten - Aisyah, Siti; , Susatyo Yuwono ,S. Psi., M. Si., Psi; , Drs. Saifuddin, M.Ag (2015)
An Islamic students who have high self esteem, she would be motivated to act in an activity and activities so as to achieve a certain result or goal. Optimism the future is important for Islamic students Tahfidz program, when Islamic students can not afford optimistic about the future to complete from memory, it will be many problems to be faced. Many factors affect the future optimism in Islamic students Tahfidz program of internal factors and external factors, including self esteem. Tahfidz program is a program designed for Islamic students who have a desire to memorize Al Qur'an (30 Juz). This study aims to determine whether there is a relation between self-esteem with optimism the future of the students Tahfidz program at the Islamic boarding house of al-Muayyad Surakarta and Ibnu Abbas Klaten. The hypothesis proposed that there is a positive relation between self-esteem with optimism the future of the Islamic students of Tahfidz program at the Islamic boarding house of al-Muayyad Surakarta and Ibnu Abbas Klaten. The subject of this research is the Islamic students of Islamic boarding house in Al Qur'an of Tahfidz Program of Al Muayyad Surakarta and Ibnu Abbas Klaten. The method of collecting data used self esteem scale with optimism the future scale. The researcher analyzed data using product moment correlation. Based on the analyzed product moment get the score of correlation coefficient ( r ) as 0,592; p = 0,000 (p < 0,01) its means the research has positive relation that many significant between self esteem with optimism the future. The effective variable from self esteem to optimism the future is 35%. Based on result of analyze the researcher know the Self Esteem variable have Empiric Average ( Rerata Empirik (RE)) 112,62 and Hypothetic Average (Rerata Hipotetik (RH)) 95 its mean the Self esteem in the subject appertain high. Based on result of analyze the researcher know the optimism the future variable have Empiric Average ( Rerata Empirik (RE)) 139,14 and Hypothetic Average (Rerata Hipotetik (RH)) 110 its mean the optimistic future in the subject appertain high. The conclusion is there are have positive relation very significant between self esteem and optimism the future of the Islamic students of Islamic boarding house in Al Qur'an of Tahfidz Program of Al Muayyad Surakarta and Ibnu Abbas Klaten. Keywords: Self Esteem, Optimism Future